Studi Komparatif Konsep Servant Leadership Stephen R. Covey Dengan Suster Kepala Taman Kanak-Kanak Katolik Sang Timur Kota Malang - Yohanes Makias De; Yoga Febriano; Yeremia Anton J. Welan; Stefanus Lau (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to conduct a comparative study of the concept of servant leadership put forward by Stephen R. Covey and its application to the Sister Head of Sang Timur Catholic Kindergarten in Malang City. Servant leadership is a leadership approach that emphasizes service to others as the main foundation of leadership. Stephen R. Covey explains this concept through his famous books, especially those related to the principles of effective and ethical leadership. This research uses a qualitative method with a case study approach. Data was obtained through in-depth interviews, observations, and analysis of articles related to the leadership activities of the Head Sister of the Sang Timur Catholic Kindergarten. Data analysis was carried out using a comparative study of Stephen R. Covey's servant leadership with the Head Sister's leadership style. The research results show that the Head Sister of Sang Timur Catholic Kindergarten consistently applies the concept of servant leadership. They highlight aspects of service, characteristics, potential development, and attention to the needs of team members as the main foundations of their leadership. Even though there may be contextual differences in its application, the concept of servant leadership remains the basis for Head Sisters in carrying out leadership responsibilities in the educational environment. This research provides further understanding regarding the application of servant leadership in the context of non-profit organizations, especially in early childhood education. This research can form the basis of practical implications for the development of more effective leadership models in educational institutions and similar organizations.